Effect of Seed Germination and Early Seedling Growth Response on Two Rice (Oryza sativa) Varieties Supplied with Different Types and Concentrations of Wastewater in Thailand (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
With increasing concerns over water scarcity, wastewater reclamation for agricultural irrigation has gained attention. However, the use of wastewater can have both positive and negative effects on crop growth. Seed germination and early seedling growth tests are considered to accurately represent crop growth population. This study aimed to evaluate the effect of different types and concentrations of wastewater on rice seed germination and early seedling growth. Two rice varieties, SIRAJ279 and MR219, were grown in wastewater from shrimp culture, domestic sources, and cement factories at five concentrations: 0 (control), 25, 50, 75, and 100%. Seed germination percentage and germination rate index were used to evaluate seed germination analysis, while the seedling length, seedling vigor index, seedling fresh weight, seedling dry weight, and phytotoxicity percentage were used to evaluate early seedling growth analysis. Results showed that the SIRAJ279 rice variety had overall better seed quality than MR219. Rice irrigated with shrimp culture and domestic wastewater showed better results in seed germination, germination rate index, seedling length, seedling vigor index, and seedling fresh weight than those irrigated with cement factory wastewater. However, no significant difference was observed in seedling dry weight. Additionally, increased wastewater concentration had a negative effect on seed and seedling results. Seedlings grown in wastewater with a concentration of 75-100% from cement factories had the highest phytotoxicity percentage (more than 30%). Therefore, it is recommended to dilute cement factory wastewater to 50% before using it for agricultural irrigation.
Keywords: Wastewater; Rice varieties; Concentrations level; Seed germination; Seedling growth; phytotoxicity